Lampes céramiques signées Définition critique d'ateliers du Haut Empire - Bonnet, Jacqueline (Documents d'archéologie française, 1988)
This work, which summarises the author's doctoral dissertation, presents an original approach to the study of lamps from the Early Roman Empire. Using a method more often applied to the study of samian pottery, the author has carried out a systematic analysis of the associations of signature, form and decoration. The purpose of the study was to verify a hypothesis, that characteristic types could be associated with a spécifie potter's signature, and, at the same time, to identify actual workshops. The research is successful not only in demonstrating the existence of significant connections between several potters, but also in questioning the uncritical use, still frequently made, of chronoiogical typologies. The author argues for setting up reference corpora of makers stamps and decorative marks and for cataloguing characteristic forms, thus enabling the lamp to play a significant rôle in the archaeological evidence, as well as bringing to light a new craft.